2019
DOI: 10.1177/0706743719892471
|View full text |Cite
|
Sign up to set email alerts
|

Light Therapy for Patients With Bipolar Depression: Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective Bipolar disorder (BD) is challenging to treat, and fewer treatments are available for depressive episodes compared to mania. Light therapy is an evidence-based nonpharmacological treatment for seasonal and nonseasonal major depression, but fewer studies have examined its efficacy for patients with BD. Hence, we reviewed the evidence for adjunctive light therapy as a treatment for bipolar depression. Methods We conducted a systematic review of databases from inception to June 30, 2019, for randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…A meta-analysis in 259 patients with bipolar disorder showed that light therapy was associated with a significant improvement in clinician-rated depressive symptoms and clinical response compared with control conditions. 6 Our previous cross-sectional study in 181 outpatients with bipolar disorder found that higher average light intensity and longer ≥1000 lux duration in the daytime were significantly associated with reduced depressive symptoms. 9 The present study supported the results of previous studies and indicated that a 1-unit increase in average morning illuminance log lux (eg, from 148 lux to 403 lux) was associated with a 34% decrease in relapse into depressive episodes.…”
Section: Discussionmentioning
confidence: 90%
“…A meta-analysis in 259 patients with bipolar disorder showed that light therapy was associated with a significant improvement in clinician-rated depressive symptoms and clinical response compared with control conditions. 6 Our previous cross-sectional study in 181 outpatients with bipolar disorder found that higher average light intensity and longer ≥1000 lux duration in the daytime were significantly associated with reduced depressive symptoms. 9 The present study supported the results of previous studies and indicated that a 1-unit increase in average morning illuminance log lux (eg, from 148 lux to 403 lux) was associated with a 34% decrease in relapse into depressive episodes.…”
Section: Discussionmentioning
confidence: 90%
“…Light therapy has many advantages for managing CRF in clinical practice, such as low cost, few side effects, and reduced concurrent symptoms (e.g., depression). pain), and so on [13]. As a result, it is important to determine the effectiveness and acceptability of light therapies for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CBT is labor intensive since it requires professional guidance for several weeks [12]. Light therapy [13], which is another nonpharmacological intervention, has been developed in recent years to treat CRF. It consists of daily exposure to bright, uorescent light delivered via a lightbox or other device for a certain amount of time upon awaking.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Практически важным является применение оперативных способов диагностики расстройств настроения в практическом здравоохранении (интеллектуальные системы экспресс-диагностики), что позволяет своевременно выявлять лиц повышенной группы риска и в дальнейшем по отношению к ним проводить интервенционные мероприятия, направленные на повышение качества жизни [19]. Своевременная диагностика всех категорий САР у студентов позволит эффективно использовать имеющийся профилактический и лечебный потенциал [20][21][22].…”
Section: Discussionunclassified